Impact of Proteinuria and Low eGFR on Lifetime Risk of Cardiovascular Disease Death: A Pooled Analysis of Data From the Evidence for Cardiovascular Prevention From Observational Cohorts in Japan Study. (11th May 2021) - Imai, Y; Sakurai, M; Nakagawa, H; Hirata, A; Murakami, Y; Kiyohara, Y; Ninomiya, T; Ishikawa, S; Saitoh, S; Irie, F; Sairenchi, T; Kiyama, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): H20–Junkankitou [Seishuu]–Ippan–013; H23–Junkankitou [Seishuu]–Ippan–005; H26-Junkankitou [Seisaku]-Ippan-001; H29–Junkankitou–Ippan–003 and 20FA1002 OnBehalf: EPOCH-JAPAN Introduction: Absolute risk of Lifetime risk (LTR) is useful estimate for risk communication compared with short term risk or relative risk especially for young people. Proteinuria is leading cause of end-stage kidney disease (ESKD) and independent risk factor for cardiovascular disease (CVD). Although nonproteinuric renal disease is global burden of ESKD, it has been poorly focused. To date, there have been no reports of impact of proteinuria and low eGFR on LTR with the outcome of CVD death in Asian population. Purpose: We aimed to estimate LTR of CVD death stratified by the status of proteinuria and low eGFR. Methods: We used modified Kaplan-Meier approach to estimate the remaining lifetime risk of cardiovascular death based on EPOCH-JAPAN(Evidence for Cardiovascular Prevention From Observational Cohorts in Japan) database. LTR was estimated at each index age starting from 40 years for those with proteinuria and without proteinuria stratified by low eGFR, which is defined as eGFR <60 ml/min/1.73 m². Participants were classified into three groups, which were those with proteinuria (Proteinuria (+)), those without proteinuria with low eGFR (Proteinuria (-)/Low eGFR (+)), those without proteinuria without low eGFR (Proteinuria (-)/Low eGFR (-)). Results: A total of 47, 292 participants from 9 cohorts was included in the analysis. Mean follow-up period was 14.6 years with 690, 463 person years and total CVD death was 1, 075 in men and 1, 193 in women. The LTRs at the index age of 40 years were as follows: 17.7% (95% confidence interval: 15.4 – 19.0%) in Proteinuria (-)/Low eGFR (-) group, 26.2% (20.2 – 31.1%) in Proteinuria (-)/low eGFR (+) group, 24.5% (15.1 – 29.3%) in Proteinuria (+) group for men; 15.3%(13.7 – 16.5%), 29.9%(14.7 – 46.8%), 28.3%(19.4 – 34.7%) for women. Conclusions: We observed that those without proteinuria with low eGFR have equivalently high LTR with those with proteinuria. These results indicate that even in the absence of proteinuria, low eGFR has high impact on LTR. Lifestyle modification from young age is necessary to prevent from renal dysfunction.